Heat Transfer Enhancement in Coaxial Downhole Heat Exchangers: Influence of Spiral Fins at the Bottom Section - Xinliu Yang; Qiang Liu; Gui Lu (Energies)
Coaxial downhole heat exchangers (CDHEs) extract heat directly from geothermal reservoirs through a closed loop, minimizing environmental impacts. However, the heat extraction efficiency is generally lower than that of groundwater harvesting technology. This study proposes integrating spiral fins on the CDHE outer tube’s inner surface to enhance heat transfer performance. Numerical simulations demonstrate that placing spiral fins on the inner wall of the outer tube significantly enhances rotational velocity and turbulence within the annular flow channel, outperforming configurations with fins on the outer wall of the inner tube. The intensified swirling flow extends to the bottom of the CDHE, promoting effective mixing of hot and cold fluids and consequently improving the heat transfer coefficient. This study also investigates the influence of fin pitch and height on heat transfer and flow characteristics. The results show that both the Nusselt number (Nu) and flow resistance increase as fin pitch decreases, causing the performance evaluation criteria (PEC) to initially increase and then decrease. Additionally, increased fin height enhances the heat transfer coefficient, but also leads to a greater pressure drop. The optimal performance was achieved with a fin pitch of 500 mm and a fin height of 10 mm, attaining a maximum PEC of 1.53, effectively balancing heat transfer enhancement and hydraulic resistance. These findings provide guidance for the structural optimization of coaxial downhole heat exchangers.